A history of Russian Christianity. - Shubin, Daniel H. (Algora Pub., 2005)
This third volume on the History of Russian Christianity deals with the period 1725 through 1894, from the death of Tsar Peter the Great to the ascension of Tsar Nicholas II. Known as the Synodal Era of Russian Orthodoxy, this is the era of Empresses Elizabeth and Catherine the Great, the persecution of the adamant Metropolitan Arsenius, the towering figure of Konstantin Pobedonostsev, and the great tsars of 19th-century Russia. This is the era of the rise of the dissenters and sectarians. The history of Old Believers is discussed, along with the eruption of innumerable sectarian groups and their persecution, including the Iconoclasts, Judaizers, Dukhabors, Molokans, Khlisti, Skoptzi, Stundists and Mennonites, and the many other small sects. The Christian philosophies of Grigori Skovoroda and Leo Tolstoy are examined as well. This intensive history of the Christianity of Russia follows the tradition of other detailed histories that have become a permanent fixture in the literary world, such as the 3-volume History of the Crusades by Steven Runciman, the 5-volume Christian Tradition of Jaroslav Pelikan; the 6-volume Penguin History of the Christian Church; and the 3-volume History of the Byzantine State by George Ostrogorski. This set will become a staple for students and scholars of Russian history and Russian Orthodoxy. The information provided is intensive and objective, dealing with the events, people and politics of the development and expansion of Christianity in Russia. The book covers the earliest of traditions, the rise and dominance of the Russian Orthodox Church, the many dissenters and sectarians that evolved over the centuries and their persecution, and the influx of Catholicism and Judaism and other minority religions into Russia. The history covers the higher levels of ecclesiastical activity including the involvement of tsars and princes, as well as saints and serfs, and monks and mystics.